Big and Little Forms of Osteoclast Activating Factor - Gregory R. Mundy; Lawrence G. Raisz; James L. Shapiro; Janet G. Bandelin; Robert J. Turcotte (The Journal of Clinical Investigation, 1977)
We have further characterized osteoclast activating factor (OAF) using a bioassay for bone resorption which utilizes the release of previously incorporated 45Ca from fetal rat long bones in organ culture. When supernatant media from activated leukocyte cultures were concentrated on Amicon PM10 membranes (assigned molecular weight cutoff 10,000 daltons) and chromatographed on Sephadex G-50 columns, the bone-resorbing activity eluted between the molecular weight markers chymotrypsinogen (25,000 daltons) and cytochrome c (12,500 daltons). This peak of biological activity has been called big OAF. When filtrates from the PM10 membranes were concentrated on Amicon UM2 membranes (assigned molecular weight cutoff 1,000 daltons) and chromatographed on Sephadex G-50 columns, some of the biological activity eluted between the molecular weight markers chymotrypsinogen and cytochrome c (big OAF), but there was a separate peak of biological activity which eluted with [3H]proline (140 daltons). This second peak has been called little OAF. Little OAF was eluted from Bio-Gel P6 columns between the molecular weight markers calcitonin (approximately 3,500 daltons) and vitamin B12 (1,330 daltons), but was retained by Spectrapor dialysis tubing (nominal molecular weight cutoff 3,500 daltons). Big OAF was converted to little OAF by equilibration in 1 M NaCl or 2 M urea. Little OAF was self-associated back to big OAF by equilibration in buffers of low ionic strength (Tris-HCl 10-50 mM). Little OAF was extracted into the organic phase in ethyl acetate after acidification of the sample to pH 3.5. The biological activity remained in the aqueous phase after ethyl acetate extraction at pH 7.5-8.4. Little OAF has been purified more than 6,000-fold compared with the original material so that bone-resorbing activity is maximal in a sample with a protein concentration of 80 ng/ml.